Invasive evaluation in children (SEEG vs subdural grids). (April 2020) - Taussig, Delphine; Chipaux, Mathilde; Fohlen, Martine; Dorison, Nathalie; Bekaert, Olivier; Ferrand-Sorbets, Sarah; Dorfmüller, Georg
Highlights: Invasive explorations still have indications in children with focal drug-resistant epilepsies. They include mainly subdural explorations and stereoelectroencephalography. Subdural explorations are only possible when the bone is at least 2 mm thick. The choice between them should be individually-based today. Thanks to thermocoagulations, stereoelectroencephalography also offers a therapeutic option. Abstract: Designed from the 60s to the 80s for adults, and despite the development of many new techniques, invasive explorations still have indications in children with focal drug-resistant epilepsy. The main types are stereoelectroencephalography (SEEG) and subdural explorations (SDE). They provide precise information on the localization of the epileptogenic zone (EZ), its relationships with eloquent cortex, and the feasibility of performing a tailored surgical resection. Thermocoagulations, which are a diagnostic and therapeutic tool, can be performed using SEEG electrodes. Both techniques are feasible in children, with an age limitation for SEEG (which requires a bone thickness above 2 mm). The complication rate is higher with SDE. Opposed for a long time and never compared in a systematic study, they should presently be considered complementary. The indications cannot be directly inferred from those for adults, as there are pediatric particularities in the seizures' semiology, functional areas, imaging and urgent situations. We successively discuss the choice in individual cases of SEEG or SDE respectively, the specific problematic in infancy and early childhood, the schema in SEEG for cryptogenic epilepsies (in particular insular), the particularities of polymicrogyria and deeply located lesions, and finally, SEEG designed for thermocoagulations. Future improvements should include more accurate implantation schemas thanks to advanced non-invasive explorations and possibilities to perform SEEG in infants.